Connective Tissue Growth Factor (CTGF) Inactivation Leads to Defects in Islet Cell Lineage Allocation and β-Cell Proliferation during Embryogenesis - Crawford, Laura A. (The Endocrine Society, 2009)
The factors necessary for normal pancreatic islet morphogenesis have not been well characterized. Here we report that connective tissue growth factor (CTGF) is involved in the establishment of normal islet endocrine cell ratio and architecture. CTGF is a secreted protein known to modulate several growth factor-signaling pathways including TGF-β, BMP, and Wnt. Although its role in pancreatic diseases such as pancreatitis and pancreatic cancer are well documented, a role for CTGF in normal pancreas development and function has heretofore not been examined. Using a lacZ-tagged CTGF allele, we describe for the first time the expression pattern of CTGF in the developing pancreas and the requirement of CTGF for normal islet morphogenesis and embryonic β-cell proliferation. CTGF is highly expressed in pancreatic ductal epithelium and vascular endothelium, as well as at lower levels in developing insulin(+) cells, but becomes down-regulated in β-cells soon after birth. Pancreata from CTGF null embryos have an increase in glucagon(+) cells with a concomitant decrease in insulin(+) cells, and show defects in islet morphogenesis. Loss of CTGF also results in a dramatic decrease in β-cell proliferation at late gestation. Unlike CTGF null embryos, CTGF heterozygotes survive past birth and exhibit a range of islet phenotypes, including an intermingling of islet cell types, increased number of glucagon(+) cells, and β-cell hypertrophy.